Problems and prospects of seafood exporters in Ernakulam district, Kerala - Hari Prakash A (College of Co-operation, Banking and Management, 2017)
Indian fisheries and aquaculture are important sectors of food production providing nutritional security to the food basket, contributing to the agricultural exports and engaging about fourteen million people in varied activities. With diverse resources ranging from deep seas to lakes in the mountains and more than 10 percent of the global biodiversity in terms of fish and shellfish species, the country has shown continuous and sustained growth in fish production since Independence. Constituting about 4.4 percent of the global fish production, the sector contributes to 1.07 percent of the GDP and 4.7 percent of the agricultural GDP. The total fish production of 6.4 million metric tonnes presently has nearly 55 percent contribution from the inland sector and nearly the same from culture fisheries. Paradigm shifts in terms of increasing contributions from inland sector and further from aquaculture are significant over the years, with high growth rates. The different facets of marine fisheries, coastal aquaculture, and fisheries are increasingly being diversified, contributing to food, health, economy, exports, employment and tourism of the country. The present chapter intends to summarise the findings in the foregoing comprehensive analysis. It seeks to make a set of suggestions while highlighting various aspects of production and exports, it also analyses factors contributing to the exports of seafood exports in Ernakulum District. This study makes an effort to bring out the problems and prospects of the marine fishery sector, it further makes some indication for future research.